Formation and Maintenance of the GEOTRACES Subsurface‐Dissolved Iron Maxima in an Ocean Biogeochemistry Model. Issue 6 (10th June 2018) - Pham, Anh L. D.; Ito, Takamitsu
Abstract : Recent GEOTRACES transects revealed basin‐scale patterns of dissolved iron in the global oceans, providing a unique opportunity to test numerical models and to improve our understanding of the iron cycling. Subsurface maxima of dissolved iron in the upper ocean thermocline are observed in various transects, which can play an important role in regulating marine productivity due to their proximity to the surface euphotic layer. An ocean biogeochemistry model with refined parameterizations of iron cycling is used to examine the mechanisms controlling the formation and maintenance of these subsurface maxima. The model includes the representation of three iron sources including dust deposition, continental shelves, and hydrothermal vents. Two classes of organic ligands are parameterized based on the dissolved organic matter and apparent oxygen utilization. Parameterizations of particle‐dependent scavenging and desorption are included. Although the model still struggles in fully capturing the observed dissolved iron distribution, it starts reproducing some major features, especially in the main thermocline. A suite of numerical sensitivity experiments suggests that the release of scavenged iron associated with sinking organic particles forms the subsurface‐dissolved iron maxima in high‐dust regions of the Indian and Atlantic Oceans. In low‐dust regions of the Pacific basin, the subsurface‐dissolved iron extrema are sustained by inputs from the continental shelves or hydrothermal vents. In all cases, subsurface ligands produced by the remineralization of organic particles retain the dissolved iron and play a central role in the maintenance of the subsurface maxima in our model. Thus, the parameterization of subsurface ligands has a far‐reaching impact on the representation of global iron cycling and biological productivity in ocean biogeochemistry models. Key Points: An ocean biogeochemistry model is used to better understand the extrema of subsurface‐dissolved iron observed in the GEOTRACES transects The iron maxima are formed by release of scavenged iron in high‐dust regions and by sedimentary or hydrothermal inputs in low‐dust regions Dissolved iron is sensitive to the pattern and binding strength of the subsurface ligand